Between Real and Phantasy: Encouraging Creativity in the First Year Architectural Education Through Fairy Tales. - Aras, Lerzan (International Journal of Art & Design Education, 2024)
The first year architectural education is based on understanding the nature of creativity in design thinking, which serves to build a solid base for a real design process; and in studios several methods are used to develop it. This study aims to discuss how using fairy tales can serve as a tool for encouraging creativity in first year design studios. It is based on a 6‐week‐long basic design II summer school course where 20 architecture and interior architecture students were asked to write fairy tales in a fantasy genre and visualise their fairy tale environment. At the end of this experimental study, we learned four important lessons: (a) when Gen Z students meet design issues first, they can be more involved and interested if they are given the opportunity to reveal their dreams and imaginations without any restriction; (b) they can show their open‐mindedness, and accept the fact that a good presentation performance even with hand drawing is possible, without using technological tools; (c) fairy tales with their unique structures can lead them to advance their "out of the box" thinking. Combining phantasy with reality might be a good tool for liberating the power of imagination which ultimately can bring good design thinking abilities and enhanced creativity, and finally (d) a further study about how they implemented this experiment in their second year design problem is worthy of further analysis.